PROPOSED AQUIFER VULNERABILITY ASSESSMENT INCORPORATING FRACTURED ROCK - Lubianetzky, Theresa A. (My University, 2015)
Much of southern Ontario relies on groundwater in fractured rock aquifers as a municipal drinking water source, thus the vulnerability of these sources is of importance from public health, economic, and environmental perspectives. Aquifer vulnerability assessments serve as visual communication tools useful in efficiently allocating resources for the establishment of new drinking water sources, hydrogeological characterization, and source water protection planning decisions. Examples of current vulnerability assessments include: DRASTIC, GOD, EPIK, AVI, COP and ISI. These vulnerability assessment methods either fail to quantitatively incorporate characteristics of fractured rock and preferential pathways, or they account for only heavily karstified areas; none are suited to the fractured rock formations in Ontario. The goal of this work is to incorporate fractured rock characteristics in a new aquifer vulnerability assessment method using readily attainable quantitative data to produce an inexpensive and straightforward regional aquifer vulnerability map highlighting hydrogeological areas that are more fundamentally prone to contamination than others. This proposed method is applied to the Acton-Georgetown study area in southern Ontario, along with the AVI and DRASTIC methods for comparison. The AVI and DRASTIC vulnerability assessments yield very different results from each other, and the proposed method demonstrates the heavy influence that fractured rock has on the vulnerability of the study area. The heterogeneity of variables used in some of the methods created difficulty in the interpolation of point data, rendering the use of generalized spatial data more valuable. These results and the corresponding limitations and recommendations for future improvements are discussed in light of these conclusions.
PROPOSED AQUIFER VULNERABILITY ASSESSMENT INCORPORATING CHARACTERIZATION OF FRACTURED ROCK ENVIRONMENTS IN SOUTHERN ONTARIO
Keywords: vulnerability mapping; fractured rock; groundwater protection; Ontario